Impact assessment of COVID-19 and PMO15 on labour in the plantation-wood processing sector in Lao PDR with policy recommendations: https://doi.org/10.69692/SUJMRD0802176 - Phonetip, Khamtan; Smith, Hilary; Boupha, Latsamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The primary objective of this research was to 1) explore the impacts of COVID-19 on availability of, and demand for, labor in the plantation-wood processing sector in Lao PDR; 2) the Government and industry response measures to COVID-19; and 3) the impacts of 2016 Prime Ministers’ Order (No. 15/PM, PMO15) aimed at addressing illegal logging and controlling log exports were also considered, as representative of a similar ‘shock’ to the sector. The research, undertaken in Vientiane Capital City, adopted a mainly qualitative methodology utilizing literature reviews and semi-structured interviews to gather data from the government, industry and workers. Micro, small and medium sized companies and their employees were surveyed. The research found that Lao wood manufacturers were affected by the shutdowns in response to COVID-19 and there were follow-on effects up and down value chains. The experiences of Laos were found to be similar to those experienced in wood producing countries globally. Supply issues and access to markets were key factors impacting the ability of factories to continue to operate and retain workers. Government protection measures were effective but challenging to implement, and access to support was difficult. Impacts on male and female differed. Awareness of, and access to, mandatory social security insurance by workers was very low. Other forms of social ‘safety-net’ were more apparent and important, including company-based programs, charity, and family/self-help. Improved dissemination of information about the need for, and benefits of, social security should occur to mitigate future shocks. The high dependence on foreign workers to fill skilled jobs in the sector remains an issue. Coupled with reforms in response to PMO15, to improve factory and product standards and ongoing export restrictions, there is a need further build Lao skills and capacity. Current efforts to up-skill Lao workers for employment in emerging wood product industries must be maintained, and improved recognition of Lao-acquired competencies is needed. Market needs analysis including the development of product dossiers is required together with the building of relevant technical expertise. Without this the Lao wood processing sector will be remain vulnerable to future shocks.